"A past that won't pass" : Stalin's museum sales in a transformed global context - Bayer, Waltraud (Journal for art market studies, 2018)
In the wake of the October Revolution, the Bolsheviks embarked on a massive nationalization drive in the sphere of culture. Major art collections once belonging to the court, the nobility, the bourgeoisie, and the church were confiscated and added to the state museum funds. Newly drafted and implemented expropriation and nationalization laws allowed formerly private art property to be then sold abroad. The Soviet art sales of the interwar period were disputed: Russian émigrés sued the Soviet government and its Western partners for illegally profiting from auctioning off their rightful private property. To this date, the sales constitute a complex, politically and legally controversial matter. Long taboo, thorough research made possible by perestroika centered notably on the very institutions that suffered the greatest losses - the Hermitage and the Palace-Museums in and around St. Petersburg, and to a lesser extent Moscow institutions. Post-Soviet museum research has yielded impressive results: Above all, it has produced a series of (mostly uncensored, unabridged) publications of edited archival funds. This relates to Jewish collections seized by the National Socialists, to Soviet émigré collections as well as to collections and museum funds of the former Soviet republics. Contemporary Russia regrets the loss of its national heritage; efforts to repurchase art sold in the interwar period are now financed by Russia’s economic elite.